2013
DOI: 10.1089/neu.2012.2565
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aromatase Genetic Variation on Hormone Levels and Global Outcome after Severe TBI

Abstract: Although experimental traumatic brain injury (TBI) studies support estradiol as a neuroprotectant and potent stimulator of neuroplasticity, clinical studies suggest a negative association between endogenous estradiol profiles and mortality/poor outcomes. However, no studies have evaluated associations with cerebral spinal fluid (CSF) hormone profiles and aromatase gene (cytochrome P450 [CYP]19A1) variability on clinical TBI outcomes. We evaluated 110 adults with severe TBI. Average and daily estradiol, testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Similar elevations and effects on outcome have been reported in a variety of neurological conditions, including septic shock, bacterial meningitis, post-traumatic stress disorder, Alzheimer disease, depression, and multiple sclerosis. [47][48][49][50][51][52] This study further extends previous work 33,34 by systematically attempting to elucidate the origins and implications behind endogenous hormone profiles after TBI. This goal was accomplished by identifying temporal CSF hormone profiles, investigating correlations between serum and CSF hormone levels, and examining injury-specific relationships between CSF progesterone and cortisol levels.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Similar elevations and effects on outcome have been reported in a variety of neurological conditions, including septic shock, bacterial meningitis, post-traumatic stress disorder, Alzheimer disease, depression, and multiple sclerosis. [47][48][49][50][51][52] This study further extends previous work 33,34 by systematically attempting to elucidate the origins and implications behind endogenous hormone profiles after TBI. This goal was accomplished by identifying temporal CSF hormone profiles, investigating correlations between serum and CSF hormone levels, and examining injury-specific relationships between CSF progesterone and cortisol levels.…”
Section: Discussionmentioning
confidence: 59%
“…While high serum estradiol levels are associated with poor outcome after severe TBI and other populations with significant trauma, 33 higher CSF estradiol/ testosterone ratios are linked to better outcomes and support the neuroprotection hypothesis for estradiol. 34 So while it is possible that supplemental progesterone may be metabolized to cortisol and augment both peripheral and CNS glucocorticoid levels, it is also possible that progesterone supplementation may instead offset any potential negative effects of augmented CNS cortisol with its pleiotropic neuroprotective effects in the CNS and conversion to other hormones with neuroprotective qualities. In fact, it has been recently suggested that progesterone secretion in astrocytes can protect them from corticosterone-induced damage in rats.…”
Section: Santarsieri Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…69 Studies show that factors including mitochondrial polymorphisms, 70 aromatase genetic variation 71 and glucose variability 72 may impact 1376 ZHANG ET AL.…”
Section: Comparison With Other Models and Translational Relevancementioning
confidence: 99%
“…SNP results from a substitution, deletion, or insertion of a base in the genetic code. [42][43][44][45][46] The two most studied types of epigenetic changes that influence recovery from TBI (often in animal models) involves methylation, when a molecule of DNA is capped by a methyl group that prevents transcription (essentially turning the gene "off").…”
Section: Genomic Variations Affecting Outcomesmentioning
confidence: 99%